Where and why can expatriates vote in regional elections? A comparative analysis of regional electoral practices in Europe and North America. Issue 4 (12th March 2019) - Arrighi, Jean-Thomas; Lafleur, Jean-Michel
ABSTRACT: The article constitutes the first systematic attempt to survey and account for the enfranchisement of non-resident citizens in regional elections. Shifting the focus away from the state to the regional demos, it is divided into two parts. First, it examines whether the spectacular horizontal diffusion of external voting legislation widely observed in existing scholarship has also spread vertically to regional elections, through a comparative overview of the conditions of eligibility to the regional franchise in 292 American and European regions. The remarkable diversity of regional electoral arrangements both within and across states calls for a more in-depth explanatory analysis of the 'micro-foundations of diaspora policy' in specific regions. The second part thus compares two negative cases, Flanders and Scotland, where expanding the franchise to expatriates has been seriously considered and yet ultimately failed. It goes on to examine the frustrated outcome in the light of three dimensions of the political opportunity structure: whether the region has the power to alter the composition of the demos (self-determination powers), the expected electoral gains and losses among political parties within the regional party system (electoral interests), and the (in)compatibility of extending the suffrage to expatriates with the pursuit of autonomy goals (self-determination aims).